2016
DOI: 10.1177/0363546516662455
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Single-Blind, Placebo-Controlled Trial of Bone Marrow Aspirate Concentrate for Knee Osteoarthritis

Abstract: Early results show that BMAC is safe to use and is a reliable and viable cellular product. Study patients experienced a similar relief of pain in both BMAC- and saline-treated arthritic knees. Further study is required to determine the mechanisms of action, duration of efficacy, optimal frequency of treatments, and regenerative potential. Registration: ClinicalTrials.gov record 12-004459.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
238
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(255 citation statements)
references
References 59 publications
(70 reference statements)
7
238
0
10
Order By: Relevance
“…Five studies evaluated cBMA in the treatment of knee osteoarthritis (OA) summarized in Table 3[20-24]. Only two studies evaluated the efficacy of cBMA without an adjunctive procedure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies evaluated cBMA in the treatment of knee osteoarthritis (OA) summarized in Table 3[20-24]. Only two studies evaluated the efficacy of cBMA without an adjunctive procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies evaluated the efficacy of cBMA without an adjunctive procedure. One reported better clinical outcomes at one week and three months in patients who received cBMA but found no difference in these scores after six months[24]. One study reported significant clinical improvements but found that 76% of patients had abnormal International Cartilage Repair Society repair scores[23].…”
Section: Resultsmentioning
confidence: 99%
“…As described by Hernigou et al [34] and later by Shapiro et al [35], briefly, appropriate local anesthesia of the skin and subcutaneous soft tissues should be administered. Then, a 1-cm stab incision was performed over iliac crest.…”
Section: Bone Marrowmentioning
confidence: 99%
“…An 11-gauge, 11-cm Jamshidi needle was used to aspirate the bone marrow. Effort was taken to use a parallel approach, with the needle directed parallel to the iliac wing between the inner and outer tables, and the needle was subsequently withdrawn and repositioned [34,35] (Figure 4). The marrow aspirates was then passed through a sterile filter into a separate compartment to remove particulate matter.…”
Section: Bone Marrowmentioning
confidence: 99%
See 1 more Smart Citation